Mitochondrially-mediated toxicity of bile acids - Palmeira, Carlos M. (2004)
In the healthy hepatocyte, uptake of bile acids across the basolateral membrane and export via the canalicular export pump, are tightly coupled. Impairment of bile formation or excretion results in cholestasis, characterized by accumulation of bile acids in systemic blood and within the hepatocyte. When the concentration of bile acids exceeds the binding capacity of the binding protein located in the cytosol of the hepatocyte, bile acids induce apoptosis and necrosis, by damage to mitochondria. Mitochondria play a central role on the toxicity of bile acids. In this article, we review the published literature regarding bile acid effects on cell function, especially at the mitochondrial level. In patients with cholestatic liver disease, the extent of hepatocyte damage caused by intracellular accumulation of bile acids appears to be delayed by ingesting a hydrophilic bile acid. However, its effects on disease progression are not completely clarified. Therefore, identification of the mechanisms of cell injury will be of clinical utility, helping in the development of new therapeutic strategies. The goal of this review is to include a fresh consideration of all possible targets and integrating pathways that are involved in cholestasis, as well as in the benefits of bile acid therapy.